2007
DOI: 10.1111/j.1447-073x.2007.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuft cells

Abstract: Tuft cells, also known as brush cells, are widespread in the hollow organs of the digestive tract including the duct system of the salivary gland and in the respiratory tract, from simple vertebrates to humans. The shape of tuft cells varies from pear-shaped, to barrel-shaped and goblet-shaped, apparently depending on the plane of section. The most characteristic morphological features of tuft cells are their long and blunt microvilli, which have prominent rootlets, and a well developed tubulovesicular system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 76 publications
(190 reference statements)
3
77
0
Order By: Relevance
“…However, previous reports have suggested that tuft cells are often found in close proximity to neurons (14,18,39), and our collaborators have demonstrated that functional innervation regulates epithelial homeostasis and response to injury (52). Indeed, we found that DCLK1 + cells were sustained when organoids were cocultured with neurons and therefore represent, to the best of our knowledge, the first cell type that cannot be generated in organoid cultures in the absence of nonepithelial niche signals.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…However, previous reports have suggested that tuft cells are often found in close proximity to neurons (14,18,39), and our collaborators have demonstrated that functional innervation regulates epithelial homeostasis and response to injury (52). Indeed, we found that DCLK1 + cells were sustained when organoids were cocultured with neurons and therefore represent, to the best of our knowledge, the first cell type that cannot be generated in organoid cultures in the absence of nonepithelial niche signals.…”
Section: Discussionmentioning
confidence: 58%
“…These results suggested that nonepithelial signals might be critical for tuft cell maintenance and longevity in organoid cultures. Given that previous reports suggested an association between epithelial tuft cells and neuronal structures (14,18,39), we hypothesized that neuronal input might support tuft cell survival in colonic, intestinal, and gastric organoid cultures. To test this hypothesis, we established a coculture system of primary neurons isolated from the spinal cord (40) To test whether functional innervation was associated with tuft cell survival in vivo, we examined paired biopsies from intestinal transplant patients (n = 2) and found that while the transplanted graft (which was extrinsically denervated) lacked DCLK1 + cells, the endogenous intestine (which was normally innervated) had a normal complement of DCLK1 + cells (Supplemental Figure .…”
Section: Dclk1 + Cells In In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Goblet cells secrete mucins and thereby establish and maintain the protective mucus layer (Kim and Ho, 2010). Tuft cells comprise a rare cell population marked by doublecortin-like kinase 1 (Dclk1) expression (Gerbe et al, 2011) and are implicated in chemoreception (Gerbe et al, 2012;Sato, 2007). Enteroendocrine cells are the hormone-producing cells in the intestine.…”
Section: Introductionmentioning
confidence: 99%